Marketing Mix Strategy (7P) in Increasing Sales Volume (Study on R&C Digital Printing Surabaya) - Ratna Adisty Firnanda Firnanda; Lia Nirawati (International Journal of Social, Economic, and Business, 2025)
The increasing competition in the digital printing industry demands businesses to implement effective marketing strategies to enhance their sales volume. This research examines the role of the marketing mix (7P) strategy—Product, Price, Place, Promotion, People, Process, and Physical Evidence—in increasing the sales volume at R&C Digital Printing Surabaya. The study employs a qualitative descriptive method with SWOT analysis to evaluate the internal and external factors influencing the company’s marketing strategy. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that R&C Digital Printing is positioned in the Growth Quadrant of the SWOT matrix, indicating strong internal capabilities and external opportunities. Key strategies include improving service quality, competitive pricing, expanding market reach through digital platforms, and optimizing promotional efforts via social media and partnerships. The study concludes that the marketing mix (7P) significantly contributes to enhancing sales volume when integrated effectively with digital marketing strategies. The implications suggest that businesses in the digital printing sector should continuously adapt their marketing strategies to market trends and customer preferences to maintain competitiveness and growth.